Simultaneous translation and rotation tracking design for sharp corner, obstacle avoidance, and time-varying terrain by hierarchical adaptive fixed-time saturated control. (December 2021) - Hwang, Chih-Lyang; Weng, Fan-Chen; Hung, Wei-Hsuan; Wu, Fan; Jan, Chau
Abstract: To fulfill the advantageous characteristics of omnidirectional mobile service robot (OMSR), i.e., simultaneous translation and rotation, the proposed hierarchical adaptive fixed-time saturated control (HAFTSC) is designed and implemented. To begin with, the path tracking model of an OMSR, including kinematics, mechanical dynamics with the friction of each wheel and the transformation between OMSR's and world coordinates, and motor dynamics, is achieved. According to the model's feature, the adaptive fixed-time virtual reference input (AFTVRI) for indirect mode is first designed to obtain the assigned task, and then an adaptive fixed-time tracking control (AFTTC) is designed to deal with high frequency motion behaviors, e.g., sharp corner tracking, obstacle avoidance, and time-varying terrain. The main features of the proposed control contain the nonlinear switching surface and nonlinear switching gains such that under suitable conditions the zero pose error is achieved at the expense of a compromised chattering input. Finally, compared experiments between nonlinear and constant switching gains, including the piecewise straight path with 90 ° corner, one obstacle or three mats on the desired path, validate the potency and robustness of the proposed control.